In vitro antioxidant activities and gas chromatography-mass spectrometry (GC-MS) analysis of phenolics in extracts of Dialium indum var. indum L. fruit - Muhamad Faris bin Osman (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2017)
Chronic diseases are prevalent in modern population nowadays and wild fruits have been studied to be good sources of antioxidants, which can be related to reduced risk of developing these diseases. The fruit of Dialium indum var. indum L. or locally known as 'keranji' from the family Fabaceae is one of the wild fruits of Malaysia. This study investigated the antioxidant content, in vitro antioxidant activities, and phenolic composition of D. indum var. indum L. fruit. The proximate content of antioxidants in the exocarp, mesocarp, and seed crude extracts and fractions of D. indum var. indum L. fruit was measured using the total phenolics content (TPC), total flavonoids content (TFC), and cupric ion reducing antioxidant capacity (CUPRAC) assays, and their in vitro antioxidant activities were evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity and linoleic acid peroxidation inhibition assays. Gas-chromatography-mass spectrometry (GC-MS) analysis was carried out for antioxidant active extracts and fractions obtained from column chromatography fractionation of antioxidant active extract of D. indum var. indum L. fruit part. Of the twelve different extracts of D. indum fruit parts, exocarp dichloromethane fraction (EDF) and seed methanol fraction (SMF) showed the highest TPC, TFC, and CUPRAC, and the strongest in vitro antioxidant activities as assessed by DPPH radical scavenging and linoleic acid peroxidation inhibition assays. TPC of the various extracts was found to have positive correlation with CUPRAC, indicating the usefulness of CUPRAC as a method for proximate analysis of antioxidants content. GC-MS analysis of trimethylsilyl (TMS)-derivatized EDF showed that its phenolic antioxidants content was higher in comparison with TMS-derivatized SMF, with detection of nine phenolic antioxidants, namely vanillic acid, syringic acid, ferulic acid, isoferulic acid, sinapic acid, vanillin, syringic aldehyde, p-hydroxybenzaldehyde, and coniferyl aldehyde in the TMS-derivatized EDF. Fractionation of EDF using normal phase column chromatography yielded five antioxidant-rich polar subfractions labelled as Di-21, Di-22, Di-24, Di-25, and Di-26, which showed stronger DPPH radical scavenging activities than EDF. Further GC-MS analysis of these five TMS-derivatized subfractions detected the presence of other four phenolic antioxidants, identified as p-hydroxybenzoic acid, homovanillic acid, p-coumaric acid, and sinapic aldehyde. Observation of sinapic and vanillic acid content in EDF and its five subfractions with their DPPH radical scavenging activities suggested the synergistic effect of sinapic acid and antagonistic effect of vanillic acid with their DPPH radical scavenging activities. Identification of thirteen phenolics in EDF evidenced that the exocarp of D. indum fruit is a good source of antioxidants, which may protect the body against deleterious effects of oxidative stress that can cause development of chronic diseases.